An Analytical Solution of the Generalized Heat Equation Using the Offset Fractional Fourier Transform - Nasrullah Bachtiar; St. Nurhilmah Busrah; Fitriyani Syamsuddin; Wahyuni Ekasasmita (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
In the present work, the main objective is to explore the solution of generalized heat using the offset fractional Fourier transform. The offset fractional Fourier transform is introduced, related theorems and essential properties are collected. Some examples are presented to illustrate the effectiveness and efficiency of the proposed method.